Talking Stick Learning Model, How Significant Has the Impact on the PGSD Students’ Speaking Skills? - Suseno, Loviniantika Cahyaning; Haryanto, Haryanto; Anafiah, Siti (Universitas Negeri Malang, 2020)
This study aims to identify differences in the PGSD students’ speaking skills with and without talking stick learning model. This study uses a quantitative approach with a quasi-experimental design. The population was all students in the 4th semester with a total of 324 students. It involved 78 sample students selected using purposive sampling. Data were collected using speaking tests, observations, and interviews. The collected data were then analyzed using the Mann Whitney test. The result showed the Sig value of 0.000 which is lower than 0.05 and the average improvement in speaking skills of the experimental group is higher than the control groups. In conclusion, there are significant differences between students who received the talking stick learning model and those who did not